Sensitivity and Specificity of Plasma ALT, ALP, and Bile Acids for Hepatitis in Labrador Retrievers. (23rd May 2017) - Dirksen, K.; Burgener, I.A.; Rothuizen, J.; van den Ingh, T.S.G.A.M; Penning, L.C.; Spee, B.; Fieten, H.
Abstract : Background: Biochemical indicators for diagnosing liver disease are plasma alanine aminotransferase activity (ALT), alkaline phosphatase activity (ALP), and bile acid concentration (BA). Objectives: To determine the sensitivity and specificity of ALT, ALP, and BA for detecting primary hepatitis (PH) in clinically healthy Labrador retrievers and investigate whether ALT and ALP can discriminate between dogs with PH and nonspecific reactive hepatitis (RH). Animals: 191 clinically healthy and 51 clinically ill Labrador retrievers with hepatic histopathology. Methods: Retrospective study. Medical records were reviewed for ALT, ALP, preprandial BA, liver histopathology, and hepatic copper concentrations. Results: In 64% (122/191) of the clinically healthy Labrador retrievers, hepatic histology revealed inflammatory infiltrates. This frequency might be biased because part of them was included as first‐line relatives of dogs with copper‐associated hepatitis. Sensitivity of ALT, ALP, and BA in this population for detecting acute hepatitis was 45, 15, and 15%, respectively. For chronic hepatitis, sensitivity was 71, 35, and 13%, respectively. Specificity of ALT, ALP, and BA was >90% for AH, CH, and RH. When increased liver enzymes were present, median ALT was significantly higher in PH cases (312 U/L, range 38–1, 369) compared to RH cases (91 U/L, range 39–139) ( P < .001). There was no difference in ALP between dogs with a PH and a RH ( P = .361). Conclusions and Clinical Importance: Histopathologic abnormalities in the liver were present in the majority of apparent clinically healthy Labrador retrievers. The sensitivity of ALT, ALP, and BA for detecting acute and chronic hepatitis in this population was low. More sensitive biomarkers are needed for early detection of liver disease in apparent clinically healthy dogs.